The role of state and law in the system of Adam Smith - Lubiński, Filip (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2019)
The dominant contemporary interpretation of Adam Smith’s thought endeavors to show his anti-state attitude. According to this interpretation, Smith, as the father of economics would also be an opponent of state interference in the activity of private entities. The purpose of this work is a comprehensive presentation of the social system described by a Scottish philosopher. This task is accomplished by drawing attention to Smith’s views on the state and the law, as well as on his participation in the creation of an area of knowledge known then as political economy.In order to reconcile the seemingly inconsistent views presented in Smith’s most famous works, the main subject of this analysis are the less frequently studied Lectures on Jurisprudence. This book, which offers Smith’s views on the role of the state and law, is the key to the correct reading of the thesis put in Theory of Moral Sentiments and An Inquiry into the Nature and Causes of the Wealth of Nations. The social system emerging from these works referred to by Smith as the civil government, can in retrospect be regarded as the progenitor of liberal democracy. The state and the law play a vital role in the economic life of this system.
Keywords: Adam Smith; state; law; classical economics; etatism; liberalism